(untitled) (Journal of Educational Sciences, 2020)
Teaching is the process of shaping and developing student’s personality, knowledge, and business skills, in accordance with modern requirements. Therefore, also teachers should enrich their methods in accordance with these requirements. Game-like living situations, role playing, theatrical performances are possible tools in order to increase students’ interest and allow them to acquire the knowledge and skills which could be applied in practice in the future. The main requirements for these games are an incorporation of learners into the image of professional-pedagogical thinking. Triggering an active participation of pupils and students is a part of constructivistic teaching strategies. This article describes how to teach and explain physics and astronomy, using games, role-playing and theatric performances played by elementary school pupils. We report a long (15 years) experience developed in Poland at Nicolaus Copernicus University, and later applied in other places, including the National Science Center in Warsaw and also abroad. Methods of increasing the effectiveness of teaching using role-playing games as an element of competition at school of Kazakhstan were considered. Both experiences revealed to be very successful. Key words: teaching, game-based teaching, business games, role-playing games, constructivism.